2024
DOI: 10.1186/s41065-023-00301-z
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology to unveil the mechanism of suanzaoren decoction in the treatment of alzheimer’s with diabetes

Tao Chen,
Yining Lei,
Manqin Li
et al.

Abstract: Background Suanzaoren Decoction (SZRD), a well-known formula from traditional Chinese medicine, has been shown to have reasonable cognitive effects while relaxing and alleviating insomnia. Several studies have demonstrated significant therapeutic effects of SZRD on diabetes and Alzheimer’s disease (AD). However, the active ingredients and probable processes of SZRD in treating Alzheimer’s with diabetes are unknown. This study aims to preliminarily elucidate the potential mechanisms and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…Other evidence showed that SZRD could regulate microbiota-gut-brain axis by inhibiting the TLR4/NFκB/NLRP3 pathway so that dysbiosis of the gut microbiota in the depressive mouse model was attenuated, restoring the relative abundance of gut microbiota by decreasing the abundance of Bacteroidetes and increasing the Firmicutes phylum members ( Du et al, 2023 ). Based on results from bioinformatic analysis, network pharmacology, molecular docking, and molecular dynamics simulation, SZRD may improve cognitive performance of AD patients with diabetes through a number of potential bioactive ingredients including licochalcone A, isorhamnetin, kaempferol, quercetin, and formononetin ( Chen et al, 2024 ).…”
Section: Herbal Medicine and Admentioning
confidence: 99%
“…Other evidence showed that SZRD could regulate microbiota-gut-brain axis by inhibiting the TLR4/NFκB/NLRP3 pathway so that dysbiosis of the gut microbiota in the depressive mouse model was attenuated, restoring the relative abundance of gut microbiota by decreasing the abundance of Bacteroidetes and increasing the Firmicutes phylum members ( Du et al, 2023 ). Based on results from bioinformatic analysis, network pharmacology, molecular docking, and molecular dynamics simulation, SZRD may improve cognitive performance of AD patients with diabetes through a number of potential bioactive ingredients including licochalcone A, isorhamnetin, kaempferol, quercetin, and formononetin ( Chen et al, 2024 ).…”
Section: Herbal Medicine and Admentioning
confidence: 99%